The effects of an augmented-reality ubiquitous writing application: a comparative pilot project for enhancing EFL writing instruction. Issue 5 (4th July 2022) - Lin, Vivien; Liu, Gi-Zen; Chen, Nian-Shing
Abstract: The use of technology such as online software has been examined in English as a foreign language (EFL) writing contexts. However, few studies have incorporated context-aware ubiquitous technology into EFL writing instruction. To develop multimodal and digital literacy of target EFL undergraduates in this pilot project, the researchers designed and implemented an augmented-reality context-aware ubiquitous writing (ARCAUW) application, which aimed to increase long-term memory, motivation, and self-regulated cognition in participants' writing development. The pilot project compared the writing outcomes and learner perceptions of the proposed ARCAUW writing mode against the baseline mobile-assisted, classroom-based writing mode. The two writing modes differed in the way that metacognitive scaffolding tasks were carried out. Pre- and post-test results showed that (a) although both modes led to significant improvement in writing the process analysis essay, ARCAUW was conducive to the development of task schema in long-term memory, motivation, and self-regulation in writing, and (b) additional cognitive processing during AR-based learning led to mixed results in writing performance. It was concluded that ARCAUW should be incorporated into mobile-assisted writing courses to reach optimal instructional outcomes. Finally, a five-step procedure was offered to help EFL practitioners design and implement ubiquitous writing in their own teaching contexts.